Digital spirits in religion and media possession and performance - Lim, Alvin Eng Hui (Routledge research in religion, media and culture, 2018)
In many contemporary and popular forms of religious practice, digital technology and the spiritual are inseparable. Ranging from streaming broadcasts of spiritual possessions to screenings of mass prayer conferences in stadiums, spirits and divinities now have new forms in which they can materialise. By offering the notion of 'digital spirits', this book critically attends to the intersections of digital media and spiritual beings. It also puts forward a new performative perspective on how they interact. Taking cues from the work of Stewart Hoover and Heidi Campbell, among others, the book begins with an outline of the current debates around religion, performance and digital media. It then moves on to examine how mediality and religion, where embodied practices are carried out alongside virtual practices, work together in contemporary Asia. These case studies focus on lived religious practices in combination with various forms of media, and so help demonstrate that digital technology in particular reveals the layered processes of spirituality in practice. Gods and divinities have always relied on media to manifest, and this book is a fascinating exploration of how digital media has continued that tradition and taken it in new directions. As such, it will be of great interest to scholars of religious studies, digital media and performance studies